Cognition, Capabilities, and Incentives: Assessing Firm Response to the Fiber-Optic Revolution - Kaplan, Sarah (Academy of Management Journal, 2008)
This study examines how CEO cognition, organizational capabilities, and organizational incentives interacted to shape firm strategy during the fiber-optic revolution. I tested for these factors' association with subsequent investment in optical technologies using longitudinal data from 71 communications firms. Results show that each is separately important in shaping outcomes, and their alignment toward the adoption of a new technology leads to the greatest levels of change. In addition, cognition can compensate when organization-level factors are lacking. Considering cognition, capabilities, and incentives together contributes to a more contingent view of the conditions under which CEO cognition matters for firm strategy.